Manzuaat wa Musharadat, Uprooted and Scattered: Refugee Women Escape Journey and the Longing to Return to Syria - Rizkalla, Niveen; Adi, Suher; Mallat, Nour Khaddaj; Soudi, Laila; Arafa, Rahma; Segal, Steven P. (Frontiers in Psychology, 2021)
Objective: Violent conflict forced millions of Syrians to flee their homes to host countries. This study examines Syrian refugee women’s experiences from the war’s outset through their journey to Jordan. It addresses the toll this journey had on their lives. Methods: Twenty-four in-depth interviews were completed with Syrian refugee women who currently reside in urban areas of Jordan. Researchers translated, transcribed, and analyzed the interviews using group narrative methodology. Results: The Syrian women had unique nostalgic memories of times before the war. They experienced atrocities during the war that forced their decision to escape Syria. Their journey narratives testify of internal displacement, personal and collective traumatic journeys via legal and illegal routes. Almost all the women were placed in refugee camps during their transitions to host country residency. In Jordan, they faced diverse hurdles of displacement and extremely different realities compared to the ones they had in Syria. Despite how very different but difficult each of their journeys were, every single woman longed to return home to Syria. Conclusions: This study presents a new understanding of the role and process of the journeys undertaken and highlights the concept of “return” as the defining element for Syrian refugee women. Regardless of the hardships women endured to escape their homeland to find safety, “return” marks an ending to their horror journey and the beginning of a new journey of hope for a better future.